EFEKTIVITAS IMPLEMENTASI UNDANG UNDANG DARURAT NO.12 TAHUN 1951 DALAM MENDUKUNG TUGAS UNIT GEGANA BRIMOB - Ilham Rafsandjani (NERACA KEADILAN, 2025)
Emergency Law No. 12 of 1951 serves as an important legal foundation for actions against the illegal possession and use of firearms and explosives in Indonesia. Despite being more than seven decades old, this law is still enforced by security forces, particularly the Gegana Unit of the Mobile Brigade (Brimob), in handling various armed threats and acts of terrorism. Given the increasingly complex dynamics of crime, the effectiveness of this law’s implementation needs to be re-evaluated to ensure its alignment with modern security challenges.This study aims to analyze the extent of the effectiveness of the implementation of Emergency Law No. 12 of 1951 in supporting the duties of the Gegana Unit of Brimob, identify the obstacles encountered in the field, and formulate strategies to enhance its implementation. The research was conducted using a qualitative approach and descriptive-analytical methods through interviews, observations, and documentation studies of the operational activities of the Gegana Unit of the North Sumatra Regional Police (Polda Sumatera Utara). The results of the study indicate that this law remains relevant as a legal basis and has proven effective in supporting the operational tasks of the Gegana Unit, especially in handling cases of illegal possession of firearms and explosives. However, its implementation still faces several obstacles such as limited facilities and infrastructure, suboptimal utilization of modern technology, and low public legal awareness. Therefore, regulatory updates, capacity building of human resources, inter-agency synergy, and broader legal outreach are needed to optimize the role of this Emergency Law in the context of current national security.